2001
DOI: 10.1093/embo-reports/kve198
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active APRIL is secreted following intracellular processing in the Golgi apparatus by furin convertase

Abstract: Tumor necrosis factor (TNF) ligand family members are synthesized as transmembrane proteins, and cleavage of the membrane-anchored proteins from the cell surface is frequently observed. The TNF-related ligands APRIL and BLyS and their cognate receptors BCMA/TACI form a two ligand/two receptor system that has been shown to participate in B-and T-cell stimulation. In contrast to BLyS, which is known to be cleaved from the cell surface, we found that APRIL is processed intracellularly by furin convertase. Blockag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
172
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(178 citation statements)
references
References 29 publications
4
172
1
1
Order By: Relevance
“…Secondly, there exists a specific consensus furin-like sequence in the chromosomal organization of both APRIL and BAFF genes, which enables the release of mature forms of APRIL and BAFF [32,34]. Furthermore, the in vitro studies showed that furin can directly cleave unprocessed APRIL into the mature form and this effect can be abrogated by the furin inhibitor, chloromethylketone [35]. APRIL and BAFF play important roles in the development of atherosclerotic lesions and plaque stabilization [36e38].…”
Section: Furin In Inflammatory Responsementioning
confidence: 99%
“…Secondly, there exists a specific consensus furin-like sequence in the chromosomal organization of both APRIL and BAFF genes, which enables the release of mature forms of APRIL and BAFF [32,34]. Furthermore, the in vitro studies showed that furin can directly cleave unprocessed APRIL into the mature form and this effect can be abrogated by the furin inhibitor, chloromethylketone [35]. APRIL and BAFF play important roles in the development of atherosclerotic lesions and plaque stabilization [36e38].…”
Section: Furin In Inflammatory Responsementioning
confidence: 99%
“…The presence of APRIL mRNA suggests that APRIL was secreted because the APRIL protein exists only as a soluble form (Lo´pez-Fraga et al, 2001). The low affinity of the available commercial antibodies precluded adequate quantification of the exact amounts of APRIL in culture supernatants.…”
Section: Inhibition Of the Proliferation Of Glioblastoma Cell Lines Umentioning
confidence: 99%
“…APRIL is produced in small amounts in peripheral blood lymphocytes (PBLs) and normal tissue but is produced in much larger quantities in malignant tumours, in which it stimulates the growth of malignant cells (Hahne et al, 1998). APRIL, which is processed by furin convertase within the cell before its secretion, is detected only in soluble form (Lo´pez-Fraga et al, 2001). Roth et al (2001) reported APRIL to be present in some malignant glioblastoma cell lines, but with no stimulatory effect on cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…It was originally identified in cell lines and primary samples from various tumor lesions in 1998 and named for its capacity to stimulate the proliferation of tumor cells (Hahne et al, 1998). In contrast to most TNF family members, APRIL is processed in the Golgi apparatus into the active soluble form by a furin convertase (Lopez-Fraga et al, 2001). APRIL is expressed by a subset of immune cells that also produce B-cell activating factor (BAFF): monocytes, macrophages, (Hahne et al, 1998;Nardelli et al, 2001;He et al, 2004;Chu et al, 2007) as well as in some non-immune cells such as epithelial cells and osteoclasts.…”
Section: Introductionmentioning
confidence: 99%